Enzyme based biosensorsb for pesticides detection - Marcel, Soropogui Keamou; Jameel, Ahmed Tariq (Kulliyyah of Engineering International Islamic University Malaysia P.O. Box 10, 50728 Kuala Lumpur, Malaysia, 2016)
Pesticides are widely used as bactericides and plant growth regulators. Despite their considerable benefit in agriculture, most pesticides can persist in the environment over long period and consist severe harm to humans and many other life forms. Their undesirable effect on living organisms has become a public concern. Public concern has led to the development of various methods for the analysis of these compounds. Although the traditional Gas Chromatographic methods have great advantages for qualitative and quantitative analysis of pesticides in the environment and in food, they appear to be expensive, time consuming and requires meticulous handling and large amount of sample. As the risk of contamination becomes more important due to the massive use of pesticides, there was a need of developing rapid and easy method to ensure environmental and food quality control. Biosensor technology is being widely developed in this context. A biosensor for pesticides detection can be either based upon the measurements of the enzyme inhibition or the measurement of compounds involved in the enzymatic reaction. The methods include inhibition-based biosensors, catalytic biosensors, whole cell biosensors, immune sensors and DNA biosensors and some new trends. Studies show that biosensors display storage stability between 30–60 days. Other important factors determined are the limit of detection, response time and applications of innovative biosensors for food, water and beverage samples. This review describes the available techniques using enzyme based biosensors for pesticide detection with special reference to their detection limit and response time.